SAT0165 Real-world utilization of concomitant medications in patients initiating etanercept: a retrospective cohort study of canadian claims-level data. (15th June 2017) - Khraishi, M; Zhang, Y; Ivanovic, J; Millson, B; Brabant, M-J; Singh, E; Woolcott, J; Jones, H
Abstract : Background: Methotrexate (MTX) and prednisone (pred) are immune suppressants frequently used to treat immune-mediated inflammatory diseases (IMIDs). Etanercept is a soluble TNF receptor (humanized protein) indicated for the treatment of IMIDs, including rheumatoid arthritis (RA), psoriatic arthritis (PsA), psoriasis (PsO), and ankylosing spondylitis (AS). Limited information exists on how MTX or pred use changes in patients who initiate etanercept in real-world settings. Objectives: To evaluate whether initiation of etanercept impacts use of co-therapy with MTX or pred in Canadian patients with IMIDs. Methods: A retrospective cohort study was conducted using claims-level data from QuintilesIMS Private Drug Plan database, Ontario Public Drug Plan database, and Quebec Public Drug Plan database. Bio-naïve patients initiating etanercept between 07/2013 and 06/2015, were identified and their claims made for MTX or pred were analyzed. Patients' utilization of MTX or pred was calculated as average weekly dose in mg, and then compared in the 6-months pre versus 12-months post initiation of etanercept using a paired t-test. Differences in the presence of concomitant medications pre and post-etanercept were also examined using a paired t-test. Results: The study captured 3, 745 etanercept patients (61% female, 77% aged between 18 and 65, 84% rheumatic diseases, and 15% PsO) across Canada in the selection period. Of selected patients, 33% used MTX (n=1, 244) and 14% (n=523) used pred pre and post initiation of etanercept. In concomitant MTX patients, the average weekly dose dispensed was 25.2mg in the 6 months prior to initiation of etanercept, and 25.0mg in the 12 months following the first claim of etanercept ( p =0.7493). In concomitant prednisone patients, the average weekly dose dispensed reduced from 123mg pre-etanercept to 108mg post-etanercept initiation ( p =0.2316). 19% of patients stopped MTX (n=287) use post-etanercept initiation, compared to 36% who stopped pred use (n=289). Conclusions: In this real-world setting, approximately 1/5 of patients stopped or reduced co-therapy of MTX; and 1/3 of patients stopped or reduced co-therapy of pred following initiation of etanercept; however, those patients who remained on co-therapy showed non-significant changes in their average consumption. Further research is needed to understand the impact on overall patient outcomes and safety. Disclosure of Interest: M. Khraishi Consultant for: Pfizer Canada and Amgen Canada, Y. Zhang: None declared, J. Ivanovic: None declared, B. Millson: None declared, M.-J. Brabant: None declared, E. Singh: None declared, J. Woolcott: None declared, H. Jones: None declared